2022
DOI: 10.1111/jcpp.13741
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling global and domain‐level adaptive behavior trajectories among children with autism spectrum disorder

Abstract: Background Heterogeneity in adaptive behavior abilities among people with autism spectrum disorder (ASD) is expressed not only as uneven levels of impairment across domains, but also in the developmental trajectories of adaptive skills. We studied the question of whether, after accounting for global adaptive behavior development, we find evidence of heterogeneity in the trajectories of specific domains of adaptive behavior. Methods A sample of 504 children with ASD was obtained by combining data from two indep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…The current study focused on subdomain‐level instead of a composite measure of adaptive functioning, as research has found that the latter may obscure domain‐specific sources of variance (Farmer et al., 2022 ; Waizbard‐Bartov & Miller, 2022 ). We also examined to what extent longitudinal heterogeneity of adaptive functioning is explained by child characteristics at diagnosis and family demographics.…”
Section: Introductionmentioning
confidence: 99%
“…The current study focused on subdomain‐level instead of a composite measure of adaptive functioning, as research has found that the latter may obscure domain‐specific sources of variance (Farmer et al., 2022 ; Waizbard‐Bartov & Miller, 2022 ). We also examined to what extent longitudinal heterogeneity of adaptive functioning is explained by child characteristics at diagnosis and family demographics.…”
Section: Introductionmentioning
confidence: 99%